Skilled throwing performance: A test of the OPTIMAL theory - Sertic, J. V. L.; Avedesian, J. M.; Navalta, J. W. (International Journal of Exercise Science, 2021)
The OPTIMAL theory of motor learning postulates that autonomy support (AS), enhanced expectancies (EE), and an external focus of attention (EF) facilitate improved motor learning and performance. However, its applicability to elite-level throwing athletes has not been investigated by previous literature. The primary purpose of this study was to investigate the successive implementation of AS, EE, and EF factors on overhand throwing performance in elite collegiate softball athletes (14.44 ± 2.75 years of softball experience). The secondary purpose was to determine whether self-efficacy beliefs would be augmented by factor manipulation. Twenty-four participants threw softballs at a bullseye target during five blocks. The Baseline test (Block 1) was used to subsequently assign participants to either the OPTIMAL or control group. Three middle blocks (Block 2 to 4) followed with successive factor implementation for the OPTIMAL group and without instruction for the control group. The final block (Block 5) served as the Transfer test, at which time throwing distance was increased. During Blocks 2 to 4, the OPTIMAL group was given the choice between softballs (AS), a liberal definition of successful throwing performance (EE), and instructed to focus on the bullseye (EF). Self-efficacy beliefs were assessed after applying the factors and before all blocks. There were no significant differences between the groups in throwing accuracy or self-efficacy scores across all blocks. The results suggest that the OPTIMAL theory does not augment skilled throwing performance or alter self-efficacy in elite softball throwing, potentially attributed to a natural adoption of EF and previously high self-efficacy.